Diálogo y novela corta en el siglo XVII: La Guía y avisos de forasteros (1620) de Liñán y Verdugo - González Ramírez, David (El Colegio de México, 2020)
This article offers a revision of the different ways that critics have presented Liñán y Verdugo’s Guía y avisos de forasteros (1620). An analysis is offered based on the text’s hybrid form (dialogue, brief narratives set within the frame-work of post-prandial conversation) and its picaresque content (the dangers that the rogues, beggars and hussies, etc., represent in court). This article also relates the work to other contemporary texts in an effort to better understand its constitution as a collection of stories.